Renal outcome after simultaneous heart and kidney transplantation. Issue 7 (19th June 2019) - Toinet, Théodore; Dominique, Inès; Cholley, Irène; Vanalderwerelt, Victor; Goujon, Anna; Paret, Fanny; Bessede, Thomas; Delaporte, Véronique; Salomon, Laurent; Badet, Lionel; Boutin, Jean‐Michel; Verhoest, Gregory; et al.
Abstract: Simultaneous heart‐kidney transplant (HKTx) is a valid treatment for patients with coexisting heart and renal failure. The aim of this study was to assess renal outcome in HKTx and to identify predictive factors for renal loss. A retrospective study was conducted among 73 HKTx recipients: Donors' and recipients' records were reviewed to evaluate patients' and renal transplants' survival and their prognostic factors. The mean follow‐up was 5.36 years. Renal primary non‐function occurred in 2.7%, and complications Clavien IIIb or higher were observed in 67.1% including 16 (22%) postoperative deaths. Five‐year overall survival and renal survival were 74.5% and 69.4%. Among survivors, seven returned to dialysis during follow‐up. The postoperative use of ECMO (HR = 6.04, P = 0.006), dialysis (HR = 1.04/day, P = 0.022), and occurrence of complications (HR = 31.79, P = 0.022) were independent predictors of postoperative mortality but not the history of previous HTx or KTx nor renal function prior to transplantation. History of KTx (HR = 2.52, P = 0.026) and increased delay between the two transplantations (HR = 1.25/hour, P = 0.018) were associated with renal transplant failure. HKTx provides good renal transplant survival and function, among survivors. Early mortality rate of 22% underlines the need to identify perioperative risk factors that would lead to more judicious and responsible allocation of a scarce resource.